Endovascular Treatment of Intracerebral Giant Cell Arteritis - Simonsen, Claus Z.; Speiser, Lasse; Hansen, Ib Tønder; Jayne, David; von Weitzel-Mudersbach, Paul (Frontiers in Neurology, 2020)
Background: Giant cell arteritis (GCA) is the most common primary systemic vasculitis predominantly affecting large and medium sized vessels. In rare cases, the vasculitis can affect the vessels of the brain. Results: We describe four cases of GCA with involvement of the cerebral vessels causing stroke. These cases were unresponsive to aggressive immunosuppression and we opted to treat with endovascular balloon dilatation of the stenotic areas. The procedure was safe. The four patients were treated in nine sessions and a total of 16 vessels were treated. We observed two dissections with no clinical influence on the patients. Discussion: In patients with stroke due to progressive GCA that is non-responsive to immunosuppression, endovascular therapy is feasible.